Method for preparing storage-stable activators for glass and ceramic substrates

By pre-hydrolysis of organosilane, titanate and zirconate in ethanol, a highly storage-stable bonding accelerator composition was prepared, which solved the poor performance of the prior art under low temperature and humidity conditions, and achieved excellent bonding effect under various climatic conditions.

CN119630725APending Publication Date: 2025-03-14SIKA TECH AG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202380055513.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-06
Filing Date
2023-08-16
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

Existing bonding promoter compositions have shortcomings in storage stability and environmental friendliness, especially when used under low temperature and humidity conditions.

Method used

Pre-hydrolysis treatment is performed by adding organosilane, organotitanate and organozirconate to ethanol and adding acid and water within the appropriate pH range to prepare a highly storage-stable single-component promoting bond pretreatment composition.

Benefits of technology

The compositions prepared by the process maintain excellent bonding properties after long storage and exposure to moisture and are suitable for a variety of climatic conditions, including thermal, humid and low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005253046610000101
    Figure BDA0005253046610000101
  • Figure BDA0005253046610000141
    Figure BDA0005253046610000141
  • Figure BDA0005253046610000142
    Figure BDA0005253046610000142
Patent Text Reader

Abstract

The present invention relates to a process for preparing a bonding-promoting pretreatment composition comprising the steps of: a) providing a reaction vessel containing 100 parts by weight of an alcohol having 1 to 4 carbon atoms; b) adding at least one organosilane OS in an amount to add 0.15 to 0.8 parts by weight of silicon, and optionally adding at least one organic titanate OT in an amount to add 0.01 to 0.8 parts by weight of titanium, and optionally adding at least one organic zirconate OZ in an amount to add 0.01 to 0.8 parts by weight of zirconium; c) adding an acid A in an amount such that the resulting pH is 3.5 to 7; d) adding water in an amount at least equimolar or molar excess to the molar amount of hydrolysable silicon, titanium and / or zirconium bonding groups present in all the added organosilane OS, organic titanate OT and organic zirconate OZ, the amount of water being at most 25 parts by weight; e) optionally, adding an additional additive selected from colorants, UV markers, condensation catalysts, or stabilizers; f) optionally waiting while stirring, oscillating, and / or heating until all hydrolysable groups present in all the added organosilane OS, organotitanate OT, and organozirconate OZ are hydrolyzed. The method results in a highly storage-stable adhesion-promoting pretreatment composition that can be used in automotive glass replacement operations and enables long-lasting adhesive adhesion, with improved water stability, regardless of environmental climate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a process for preparing an adhesion-promoting pretreatment composition which is suitable as an adhesion-promoting activator, in particular for glass and ceramic substrates, as well as to the composition itself and its use. Background Art

[0002] Using adhesives such as polyurethane adhesives to bond substrates is a widely used technology in construction and manufacturing. However, some substrates (bonding substrates) may be problematic in this respect because they cannot establish enough initial bonding with certain adhesives, or the bonding is lost over time, particularly under harsh environmental conditions such as heat or humidity. For this reason, long-term use of bonding promoter compositions, also referred to as activators, is applied to such problematic substrates before the adhesive to form an intermediate layer between the substrate and the adhesive or generate a covalently bonded chemical bonding portion for the adhesive to react thereon, with the goal of improving bonding or maintaining appropriate bonding during the life of the adhesive bonding article. The particularly important field using bonding promoter compositions is automotive glass repair (AGR), because these applications relate to substrates that are difficult to bond, such as glass and ceramics, which are generally not easy to bond with conventional adhesives for the application, particularly those based on polyurethane that are most commonly used in the field. In addition, especially in AGR applications, the bonding process is usually carried out under adverse conditions (e.g., cold or humid climates), but it is always desired to form the adhesive bonding as quickly and durably as possible.

[0003] Typically, such adhesion promoting compositions are organic or aqueous solutions containing dispersed or dissolved organosilanes, once curable binder is deposited and crosslinked on the surface of substrate, it is possible to realize the ideal intermediate layer for the bonding of glass and ceramics and curable binder or the reactive groups of at least covalent attachment. More particularly, such adhesion promoting compositions are used as primers and activators, that is, as adhesion promoting undercoat or adhesion promoting cleaning compositions. Such compositions usually contain inert, volatile solvents to ensure fast drying (flash-off) (evaporation of solvent). However, the content of organic solvents is disadvantageous in terms of environmental compatibility and occupational safety. In addition, when using solvent-based silane-containing pretreatment compositions, it is usually required to add a large amount of silane hydrolysis catalysts and condensation catalysts to these compositions to ensure that these silanes react quickly enough on substrate. However, this seriously damages the storage and handling stability of such compositions, because a small amount of moisture entering the container of the composition easily causes undesirable precipitation and gelation reaction.

[0004] Aqueous adhesion promoter compositions based on organosilane and containing water as solvent are referred to as EHS-friendly substitutes for such compositions based on solvents. In addition, they are obviously insensitive to the hydrolysis caused by contact with additional water and can be easily processed. However, they also have some significant disadvantages. The problem of aqueous adhesion promoter compositions based on silane is that they have relatively low storage stability (shelf life) together with sufficient reactivity or insufficient reactivity together with sufficient storage stability. This is because the silane used has hydrolyzable functional groups, which are hydrolyzed to form silanol groups (Si-OH) when mixed with water. Such silanol groups are usually reactive and spontaneously condense each other under the formation of relatively high molecular weight condensation products, which cause the insoluble precipitate in the adhesion promoter composition and the damage of its function.

[0005] In addition, the use of aminosilanes and / or mercaptosilanes in such aqueous adhesion promoter compositions is known. The emulsification of mercaptosilanes or oligosilane-mercaptosilane mixtures in water is particularly difficult because mercaptosilanes are not water-soluble before the silane groups are hydrolyzed. In order to bring these silanes into the water, before the hydrolysis, a completely uniform distribution must be ensured. In addition, the pH must be adjusted with an acid (e.g., acetic acid) so as to slow down the condensation that occurs as a further reaction as much as possible. Therefore, silane and water must be quickly and uniformly mixed, which requires a special mixing device.

[0006] The effect is that aqueous adhesion promoter compositions are usually used as 2-component systems (e.g. Sika® from Sika Schweiz AG). -100) and requires a mixing process for mixing the two components on site before use. It is important that the two components are mixed very quickly and evenly, with very significant turbulence. For this purpose, a specially developed piece of equipment ("oscillator") is required. After formulation, the premixed product has a storage stability ("pot life") of no more than 30 days.

[0007] Another waterborne primer composition is disclosed in WO2013 / 116004. The composition combines both organosilanes and organotitanates, which further improves the adhesion-promoting properties on certain substrates compared to compositions based only on silanes. However, the combination of organosilanes and organotitanates in a one-component waterborne composition creates particularly harsh conditions regarding the storage stability of the solution, because irreversible precipitation and aggregation of silanes and titanates or their reaction products are easily observed. As taught in WO2013 / 116004, by using a large amount of stabilizing surfactants, a stable solution with durable transparency and no precipitation can be obtained. However, such a high amount of surfactants generally leads to other problems, similar to the emulsifiers further described above, such as these substances migrate onto or into the substrate surface, interfere with the bonding process or the adhesive itself, or produce subsequent bonding losses by chemical reactions in the adhesive or with the substrate.

[0008] Another major disadvantage of water-based pretreatment compositions is their limitation with regard to the application temperature. At temperatures of 0° C. or below, water-based pretreatment compositions can no longer be used, since the evaporation of the water is severely restricted and they may even freeze solid.

[0009] Solvent-based activators based on silanes and optionally titanates and / or zirconates are disclosed, for example, in WO 2008 / 061981. The adhesion-promoting compositions disclosed in this document are particularly suitable for low-temperature applications, down to temperatures of 0° or even below zero. However, the hydrolysis and crosslinking reactions of the active silanes and the further components contained therein require water, which usually originates from air humidity or water adsorbed on the surface of the substrate, and therefore proceed rather slowly. In order to accelerate the progress, large amounts of catalysts for these reactions are usually added, which, however, in turn leads to a significant sensitivity to moisture and a highly reduced storage stability, especially once the container of the composition is opened. In addition, most of the solvents used in solvent-based activators are VOC and / or problematic in terms of EHS.

[0010] Furthermore, solvent based activators often show loss of bond when the adhesive bond is severely exposed to water.

[0011] WO 2006 / 049368 A1 discloses a coating composition for improving the stain resistance and weathering resistance of a substrate. The composition is based on a blend of different organosilanes and metal oxides, isopropyl alcohol and acetic acid, a silicone-acryl-based polymer, water and an organic solvent containing different alcohols.

[0012] Therefore, it would be desirable to have a bonding promoting pretreatment composition that can be prepared as a consumer-friendly one-component composition in a simple process using readily available raw materials and does not require moisture protection during preparation. It would be desirable to use such a composition in hot and cold climates without restriction. In addition, it would be desirable that such a composition be completely storage stable for months up to years without precipitation or discoloration, even when its container is repeatedly exposed to air, and still show excellent bonding promoting properties, especially for AGR applications, and beneficial EHS properties. In addition, the adhesive bond formed with such a composition should have excellent resistance to water immersion. Summary of the invention

[0013] The object of the present invention is therefore to provide a simple process for preparing a highly storage-stable, silane- and optionally titanate-based adhesion-promoting pretreatment composition which is insensitive to moisture and is available as a ready-to-use one-component composition and is EHS-friendly and compatible with slow-curing or fast-curing polyurethane adhesives and can be applied in any climate, including hot environments, humid environments or cold environments with temperatures down to well below 0° C., is capable of forming water-insensitive adhesive bonds and shows excellent and lasting adhesion-promoting properties even after long periods of storage and exposure to air.

[0014] It has now been found that, surprisingly, this object can be achieved by a stepwise process as defined in claim 1: the required ingredients are added to an alcohol having 1 to 4 carbon atoms, preferably ethanol, in particular as only solvent, and the active ingredients are prehydrolyzed, resulting in an extremely storage-stable one-component adhesion-promoting pretreatment composition which shows no precipitation or other degradation even after repeated exposure to air and moisture and which maintains both its composition stability and its adhesion-promoting properties after extended storage of up to several months or more. The simple and cost-effective process of the invention requires no special equipment and can be successfully carried out using cheap and widely available raw materials.

[0015] The adhesion-promoting composition obtained by the process of the present invention is a highly effective, adhesion-promoting pretreatment for adhesive bonding operations, particularly when adhesives based on polyurethane polymers or polymers having reactive silane groups are used, and especially on substrates including glass or ceramics.

[0016] Surprisingly, the adhesion promoting compositions prepared by the process of the present invention equal or even exceed the prior art water-based or solvent-based adhesion promoters in adhesion promoting ability and water resistance, and they do not lose their adhesion promoting properties after extended storage or even exposure to moisture or air.

[0017] Therefore, the present invention relates to a method for preparing an adhesion-promoting pretreatment composition comprising the following steps:

[0018] a) providing a reaction vessel containing 100 parts by weight of an alcohol having 1 to 4 carbon atoms, in particular ethanol;

[0019] b) adding at least one organosilane OS in an amount to add 0.15 to 0.8 parts by weight of silicon, and optionally adding at least one organotitanate OT in an amount to add 0.01 to 0.8 parts by weight of titanium, and optionally adding at least one organozirconate OZ in an amount to add 0.01 to 0.8 parts by weight of zirconium;

[0020] c) adding an acid A, in particular acetic acid, in such an amount that the resulting pH is from 3.5 to 7;

[0021] d) adding water, wherein the amount of water added is at least equimolar or in molar excess to the molar amount of hydrolyzable silicon-bonded groups, titanium-bonded groups and / or zirconium-bonded groups present in all added organosilanes OS, organotitanates OT and organozirconates OZ, wherein the amount of water is at most 25 parts by weight;

[0022] e) optionally, adding further additives selected from colorants, UV markers, condensation catalysts, or stabilizers;

[0023] f) waiting, optionally with stirring, shaking, and / or heating, until all hydrolyzable groups present in all added organosilanes OS, organotitanates OT and organozirconates OZ are hydrolyzed.

[0024] It has been found that, unexpectedly, with the simple method of the present invention, a durable storage-stable solid solution of pre-hydrolyzed organosilanes, organotitanates and / or organozirconates can be prepared in an ethanol-based composition, which is highly suitable as a bonding promoter or activator for adhesive bonding operations, especially for glass or ceramic substrates. The composition obtained by the method of the present invention combines all the advantages of such pre-treatment compositions based on water and solvent-based silanes, titanates or zirconates, but does not have the inherent disadvantages common in water-based or solvent-based pre-treatment compositions. Other unexpected findings are that, even after extended storage and exposure to humid air, the composition of the present invention does not deteriorate or lose its bonding promotion. However, the composition according to the present invention shows excellent bonding promotion performance and is even compatible with fast-curing or accelerated adhesives, regardless of the climatic conditions during application.

[0025] The adhesion-promoting pretreatment composition of the invention is very generally suitable as a reactive, cleaning and bonding pretreatment for substrates, especially glass and glass ceramics, in particular for automotive glass repair or for direct glazing in automotive assembly as a pretreatment for adhesive bonding, especially with polyurethane adhesives or adhesives based on silane-functional polymers (including RTV silicones and organosilane-functional polymers), preferably one-component polyurethanes or silane-curing adhesives. DETAILED DESCRIPTION

[0026] In this document, the terms "silane" and "organosilane" refer to a group having firstly at least one hydrolyzable group, typically two or three hydrolyzable groups, preferably alkoxy or acyloxy groups, directly bonded to the silicon atom via a Si-O bond, and secondly, in particular, at least one organic group directly bonded to the silicon atom via a Si-C bond. Such silanes having alkoxy or acyloxy groups are also known to those skilled in the art as organoalkoxysilanes or organoacyloxysilanes.

[0027] Silanes have the property of undergoing hydrolysis when in contact with moisture. This forms organosilanols, i.e. organosilicon compounds containing one or more silanol groups (Si-OH groups), and this, by subsequent condensation reactions, forms organosiloxanes, i.e. organosilicon compounds containing one or more siloxane groups (Si-O-Si groups).

[0028] “Epoxysilane”, “aminosilane” and “mercaptosilane” refer to organosilanes in which the organic group has an epoxy group, an amino group and a mercapto group, respectively. Organosilicon compounds having an amino group, a mercapto group or an oxirane group are also referred to as “aminosilane”, “mercaptosilane” or “epoxysilane”.

[0029] "Primary aminosilane" refers to an aminosilane having a primary amino group (ie, an NH2 group bonded to an organic group). "Secondary aminosilane" refers to an aminosilane having a secondary amino group (ie, an NH2 group bonded to two organic groups).

[0030] The hydrolyzable group of Si-bonding is a group that can be hydrolyzed to a silanol group by hydrolysis optionally in the presence of a catalyst. The hydrolyzate is a silane in which the hydrolyzable group has been at least partially hydrolyzed, that is, at least some of the hydrolyzable group has been replaced by an OH group. The condensation product comprises the condensate of two or more such hydrolyzed silanes. These hydrolysis and condensation products of silanes are well known to those skilled in the art.

[0031] The expression "independently" here also always means independently within the same molecule if different options exist.

[0032] A substance or composition is said to be "storage-stable" or "storable" when it can be stored in a suitable container at room temperature for an extended period of time, typically at least 3 months and up to 6 months or longer, without its application or use characteristics being altered to any extent relevant to its use as a result of the storage.

[0033] In this document, the terms "mass" and "weight" are used synonymously. Thus, "weight percent" (wt%) is a percentage mass fraction, unless otherwise stated, which relates to the total composition or (depending on the context) the mass (weight) of the entire molecule.

[0034] "Room temperature" refers to a temperature of 23°C±2°C, especially 23°C.

[0035] Unless otherwise stated, all industry and official standards mentioned in this document relate to the version in force at the time of submission of the initial application.

[0036] In a first aspect, the present invention relates to a method for preparing an adhesion promoting pretreatment composition, comprising the following steps:

[0037] a) providing a reaction vessel containing 100 parts by weight of an alcohol having 1 to 4 carbon atoms, in particular ethanol;

[0038] b) adding at least one organosilane OS in an amount to add 0.15 to 0.8 parts by weight of silicon, and optionally adding at least one organotitanate OT in an amount to add 0.01 to 0.8 parts by weight of titanium, and optionally adding at least one organozirconate OZ in an amount to add 0.01 to 0.8 parts by weight of zirconium;

[0039] c) adding an acid A, in particular acetic acid, in such an amount that the resulting pH is from 3.5 to 7;

[0040] d) adding water, wherein the amount of water added is at least equimolar or in molar excess to the molar amount of hydrolyzable silicon-bonded groups, titanium-bonded groups and / or zirconium-bonded groups present in all added organosilanes OS, organotitanates OT and organozirconates OZ, wherein the amount of water is at most 25 parts by weight;

[0041] e) optionally, adding further additives selected from colorants, UV markers, condensation catalysts, or stabilizers;

[0042] f) waiting, optionally with stirring, shaking, and / or heating, until all hydrolyzable groups present in all added organosilanes OS, organotitanates OT and organozirconates OZ are hydrolyzed.

[0043] The above steps are preferably carried out in the consecutive order a) to f). It may be advantageous to include further steps between two respective steps, for example, storage or transport of an intermediate composition, or process steps such as heating, mixing, or cooling, or the addition of further ingredients.

[0044] The first step a) involves providing a reaction vessel with 100 parts by weight of an alcohol having 1 to 4 carbon atoms. These parts by weight are related to other ingredients added in subsequent steps of the process (eg, step b) or step c)).

[0045] The solvent used in step a) must be an alcohol having 1 to 4 carbon atoms. Specific examples of suitable such alcohols include methanol, ethanol, n-propanol (1-propanol), isopropanol (propane-2-ol), n-butanol (1-butanol), isobutanol (2-methyl-1-propanol), sec-butanol (2-butanol) and tert-butanol (2-methyl-2-propanol). Methanol, ethanol, isopropanol and tert-butanol are preferred among these due to their advantageously low boiling points compared to the others.

[0046] Ethanol was found to be the most preferred solvent for the process of the present invention, as it is able to dissolve all ingredients appropriately, is compatible with water, evaporates fairly quickly, and does not pose a significant EHS hazard. In addition, ethanol is particularly compatible with the substances added in step b) and allows excellent storage stability of the composition to be achieved.

[0047] Furthermore, ethanol has good cleaning and degreasing properties, which is an additional advantage when the composition prepared using the process of the present invention is used as an activator, because it not only deposits the active adhesion-promoting compound on the substrate surface, but also removes undesirable deposits such as dirt, grease and oil from the substrate.

[0048] Preferably, the alcohol having 1 to 4 carbon atoms, preferably ethanol, is the only organic solvent used in the process of the invention and subsequently in the composition prepared by the process. However, small amounts of co-solvents may be added, for example to improve substrate cleaning properties or to improve the solubility of certain ingredients.

[0049] Cosolvents are understood to mean organic solvents that are miscible with ethanol, such as other alcohols, including glycols, or ethers or ketones. However, it is preferred that such organic solvents are used only in small amounts, i.e. typically less than 10% by weight based on the total solvent content in the composition including ethanol. More preferably, the composition - except for trace amounts of alcohol produced by the hydrolysis of the alkoxysilane used in the aqueous composition - does not contain such organic cosolvents. If cosolvents are used, VOC problems are in turn increased, so it is preferred that such cosolvents (if present) do not have problems with EHS properties.

[0050] However, it is possible and may be advantageous to add an excess of water in step d) so that unreacted water remains in the composition as a co-solvent. The maximum amount of water to be added in step d) is 25 parts by weight (relative to 100 parts by weight of alcohol in step a)). Preferably, the amount of water added does not exceed 20 parts by weight.

[0051] Preferably, the total amount of water in the composition after step f) is at most 20 wt.-%, more preferably at most 15 wt.-%, based on the total composition.

[0052] Step b) of the process according to the invention involves the addition of at least one organosilane OS in an amount of 0.15 to 0.8 parts by weight of silicon, and optionally at least one organotitanate OT in an amount of 0.01 to 0.8 parts by weight of titanium, and optionally at least one organozirconate OZ in an amount of 0.01 to 0.8 parts by weight of zirconium.

[0053] These amounts will be calculated based on the added weight of silicon, optionally titanium and optionally zirconium atoms contained in the added organosilane OS, the optionally added organotitanate OT and the optionally added organozirconate OZ. By this calculation, differences between the individual (e.g., organosilanes) can be taken into account, since they may differ from each other in terms of the individual number of their functional groups. For example, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, an organosilane OS, contains 12.63 wt. % silicon, while bis(trimethoxysilylpropyl)amine, another organosilane OS, contains 16.45 wt. % silicon, based on each corresponding molecule. The amount of silicon in these two examples determines the effective amount of the active bonding component much more accurately than the total weight, since the latter may vary significantly between different organosilanes.

[0054] In a preferred embodiment, step b) involves adding 1 to 5 parts by weight of at least one organosilane OS and optionally 0.1 to 5 parts by weight of at least one organotitanate OT and optionally 0.1 to 5 parts by weight of at least one organozirconate OZ to the ethanol provided in step a). These amounts still encompass the most preferred embodiments of the organosilane OS, organotitanate OT and organozirconate OZ based on the total weight of the molecules added rather than the individual Si, Ti, or Zr atoms.

[0055] In step b), it is mandatory to add the at least one organosilane OS in an amount of 0.15 to 0.8 parts by weight of silicon to 100 parts by weight of the alcohol having 1 to 4 carbon atoms, preferably ethanol. Higher amounts have been found to adversely affect the storage stability of the composition without further improving the adhesion-promoting properties.

[0056] The organosilanes OS added to the composition in step b) each have at least one Si-bonded hydrolyzable group, which may initially have been partially hydrolyzed, but preferably not. These may be any conventional hydrolyzable groups, preferably alkoxy and acyloxy groups, and particularly preferably C1-C4-alkoxy groups. After mixing with water in step d), the hydrolyzable groups may be hydrolyzed over time. In this case, the result is a hydrolyzate in which at least some and later all hydrolyzable groups are replaced by OH groups (silanol groups). As a further reaction, condensation products may be formed to a limited extent via the silanol groups formed in the hydrolyzate. For example, the organosilanes present may also be in a completely hydrolyzed or partially hydrolyzed or even partially condensed form. However, the acid A added in step c) will prevent extensive condensation reactions.

[0057] Particularly suitable organosilanes OS are organosilicon compounds of the formula (I) or (II) or (III)

[0058]

[0059] Here R 1 is a straight-chain or branched, optionally cyclic alkylene group having 1 to 20 carbon atoms, optionally having an aromatic moiety and optionally having one or more heteroatoms, especially a nitrogen atom.

[0060] Here R 2 is H or an alkyl group having 1 to 5 carbon atoms, in particular methyl or ethyl, or an acyl group, in particular acetyl.

[0061] Here R 3 is an alkyl group having 1 to 8 carbon atoms, especially a methyl group.

[0062] Here X is H or a functional group selected from the group comprising OH, (meth)acryloyloxy, mercapto, glycidyl, epoxy, primary amine, alkylamine, secondary alkylamine or arylamine comprising primary and secondary amino groups, acylthio and vinyl, preferably in all forms of amine as described previously. For the sake of completeness, reference to acylthio in this document is to be understood as meaning the substituent Where R 4 is an alkyl group, especially having 1 to 20 carbon atoms, and the dotted line represents the substituent R 1 key.

[0063] Here X 1 is a functional group selected from the group consisting of NH, S, S2 and S4.

[0064] Here X 2 is a functional group selected from the group consisting of N and isocyanurate.

[0065] The index a here represents one of the values ​​0, 1 and 2, preferably 0.

[0066] Substituent R 1 In particular, methylene, propylene, methylpropylene, butylene or dimethylbutylene. Particularly preferred is propylene as the substituent R. 1 .

[0067] Examples of suitable organosilicon compounds of formula (I) are organosilicon compounds selected from the group comprising:

[0068] Octyltrimethoxysilane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, methyloctyldimethoxysilane;

[0069] 3-methacryloxypropyltrialkoxysilane, 3-methacryloxypropyltriethoxysilane, 3-methacryloxypropyltrimethoxysilane;

[0070] 3-Aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-amino-2-methylpropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyldimethoxymethylsilane, 4-aminobutyltrimethoxysilane, 4-aminobutyldimethoxymethylsilane, 4-amino-3-methylbutyltrimethoxysilane, 4-amino-3,3-dimethylbutyltrimethoxy trimethoxysilane, 4-amino-3,3-dimethylbutyldimethoxymethylsilane, [3-(2-aminoethylamino)propyl]trimethoxysilane (=4,7,10-triazadecyltrimethoxysilane), 2-aminoethyltrimethoxysilane, 2-aminoethyldimethoxymethylsilane, aminomethyltrimethoxysilane, aminomethyldimethoxymethylsilane, aminomethylmethoxydimethylsilane, 7-amino-4-oxaheptyldimethoxymethylsilane, N-(methyl)-3-aminopropyltrimethoxysilane, N-(n-butyl)-3-aminopropyltrimethoxysilane;

[0071] 3-Acylthiopropyltrimethoxysilane;

[0072] Vinyltrimethoxysilane and vinyltriethoxysilane.

[0073] Preference is also given to the organosilicon compounds just mentioned in which the alkoxy group is replaced by an acetoxy group, for example octyltriacetoxysilane (octyl-Si(O(O═C)CH 3 ) 3 ). Such organosilicon compounds eliminate acetic acid during hydrolysis.

[0074] Among the organosilicon compounds mentioned, preference is given to those having organic substituents bonded to the silicon atom which additionally have a functional group, ie which are not alkyl, and which conform to the formula (I) in which X is not H.

[0075] Suitable examples of organosilicon compounds of formula (II) are organosilicon compounds selected from the group comprising bis[3-(trimethoxysilyl)propyl]amine, bis[3-(triethoxysilyl)propyl]amine, 4,4,15,15-tetraethoxy-3,16-dioxa-8,9,10,11-tetrathia-4-15-disilaoctadecane (bis(triethoxysilylpropyl)polysulfide or bis(triethoxysilylpropyl)tetrasulfane), bis(triethoxysilylpropyl)disulfide.

[0076] Suitable examples of organosilicon compounds of formula (III) are organosilicon compounds selected from the group comprising tris[3-(trimethoxysilyl)propyl]amine, tris[3-(triethoxysilyl)propyl]amine, 1,3,5-tris[3-(trimethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione urea (=tris(3-(trimethoxysilyl)propyl)isocyanurate) and 1,3,5-tris[3-(triethoxysilyl)propyl]-1,3,5-triazine-2,4,6(1H,3H,5H)-trione urea (=tris(3-(triethoxysilyl)propyl)isocyanurate).

[0077] Optionally, the composition may also contain at least one tetraalkoxysilane of formula (IV)

[0078] Si(OR 4 )4(IV)

[0079] Where R 4 Independently, it is an alkyl or acyl group, especially an acetyl group, having 1 to 4 carbon atoms. Such tetraalkoxysilanes are, for example, tetramethoxysilane, tetraethoxysilane, tetraisopropoxysilane, tetrapropoxysilane, tetrabutoxysilane and tetraacetoxysilane. Tetraethoxysilane is particularly preferably considered. As in the case of aminosilanes and mercaptosilanes, tetraalkoxysilanes can undergo hydrolysis in the presence of water and optionally condense with other silanes.

[0080] The organosilane OS preferably comprises at least one organosilane or a condensate thereof having at least one Si-bonded hydrolyzable group and having at least one primary and / or secondary amino group. If more than one type of organosilane OS is to be added, these can be added sequentially without any particular order. However, it is generally also possible to add all silanes simultaneously in the form of a silane premix. These further organosilanes OS are in particular organosilanes or oligomers of these organosilanes having at least one Si-bonded hydrolyzable group and having at least one further functional group selected from alkyl, alkylene, epoxy, mercapto, hydroxyl and isocyanurate groups, including the mercaptosilanes and epoxysilanes described below.

[0081] Preferred organosilanes OS are aminosilanes, in particular X═NH2 or NH2—CH2—CH2—NH, X 1 =NH and X 2 = N. Particularly preferably, 3-aminopropyltrimethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, bis[3-(trimethoxysilyl)propyl]amine, 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltriethoxysilane and bis[3-(triethoxysilyl)propyl]amine and mixtures thereof come into consideration.

[0082] Suitable aminosilanes as organosilane OS are, in particular, aminosilanes selected from the group consisting of 3-aminopropyltrimethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-amino-2-methylpropyltrimethoxysilane, 4-aminobutyltrimethoxysilane, 4-aminobutyldimethoxymethylsilane, 4-amino-3-methylbutyltrimethoxysilane, 4-amino-3,3-dimethylbutyltrimethoxysilane, 4-amino-3,3-dimethylbutyldimethoxymethylsilane, 2-aminoethyltrimethoxysilane, 2-aminoethyldimethoxymethylsilane, aminomethyltrimethoxysilane, aminomethyldimethoxymethylsilane, aminomethylmethoxydimethylsilane, N-methyl-3-aminopropyltrimethoxysilane, N-ethyl-3-aminopropyltrimethoxysilane, N-butyl-3-aminopropyltrimethoxysilane, N-cyclohexyl-3-aminopropyltrimethoxysilane, N-phenyl-3-aminopropyltrimethoxysilane, N-methyl-3-amino-2-methylpropyltrimethoxysilane, N-ethyl-3-amino-2-methylpropyltrimethoxysilane, N-ethyl-3-aminopropyldimethoxymethylsilane, N-phenyl-4-aminobutyltrimethoxysilane, N-phenylaminomethyl-dimethoxymethylsilane, N-cyclohexylaminomethyldimethoxymethylsilane, N-methylaminomethyldimethoxymethylsilane, N-ethylaminomethyldimethoxy-methylsilane, N-propylaminomethyldimethoxymethylsilane, N-butylamino-methyldimethoxymethylsilane; N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane, bis(trimethoxysilylpropyl)amine, and analogs thereof having three ethoxy groups or three isopropoxy groups instead of three methoxy groups on silicon.

[0083] In one embodiment, the aminosilane of formula (I) is an aminosilane of formula (V)

[0084]

[0085] Where R 5 is a straight-chain or branched alkylene radical having 1 to 6 carbon atoms, in particular propylene radical, and the further substituents and indices are as defined in formula (I). 3-Aminopropyltrimethoxysilane comes into consideration here with particular preference.

[0086] In a preferred embodiment, the aminosilane of the formula (I) has secondary amino groups, in particular an aminosilane of the formula (VI) or (VII) or (VIII).

[0087]

[0088] Where R 5is a straight-chain or branched alkylene radical having 1 to 6 carbon atoms, in particular a propylene radical, and the other substituents and indices are as defined in formula (I). N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, 3-[2-(2-aminoethylamino)ethylamino]propyltrimethoxysilane and bis(trimethoxysilylpropyl)amine have been found to be particularly preferred as organosilane OS.

[0089] It has been found to be particularly advantageous when two or more aminosilanes of formula (I) are present as organosilane OS in the composition, of which preferably at least one is an aminosilane of formula (VI). Particularly preferred combinations within the organosilane OS in the composition are aminosilanes of formula (VI) and aminosilanes of formula (VIII).

[0090] In one or more embodiments, the at least one aminosilane or its hydrolysis product is present in the composition of the invention after step d) in an amount of 0.5% to 5% by weight, preferably 1% to 4% by weight, particularly preferably 2% to 3% by weight, based on the total composition after step d).

[0091] In a preferred embodiment, the organosilane OS comprises at least one epoxysilane. Epoxysilanes suitable as organosilane OS have at least one epoxy group (eg glycidyl) and at least one Si-bonded hydrolyzable group. The epoxy group is preferably a glycidyl group or an epoxycyclohexyl group, especially a glycidyl group.

[0092] Preferred epoxysilanes are (epoxyalkoxy)alkyltrialkoxysilanes and 3-glycidylpropyltrialkoxysilanes. γ-Glycidylpropyltrimethoxysilane is particularly preferred. Preferred representatives of these substance classes are β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and β-(3,4-epoxycyclohexyl)ethyltriethoxysilane, and also 3-glycidylpropyltrimethoxysilane and / or 3-glycidylpropyltriethoxysilane. More preferably, 3-glycidylpropyltrimethoxysilane and / or 3-glycidylpropyltriethoxysilane are used as organosilane OS.

[0093] In one or more embodiments, the at least one epoxysilane or its hydrolyzate is present in the composition of the invention after step f) in an amount of 0.1% to 2% by weight, preferably 0.2% to 1.5% by weight, particularly preferably 0.5% to 1% by weight, based on the total composition after step d).

[0094] In a preferred embodiment, the organosilane OS comprises at least one mercaptosilane.

[0095] Mercaptosilanes suitable as organosilanes OS have at least one mercapto group, for example mercaptopropyl, and at least one Si-bonded hydrolyzable group and are preferably mercaptofunctional organoalkoxysilanes, i.e. mercaptosilanes which carry C1 to C4 alkoxy groups on the hydrolyzable silane group. Mercaptofunctional organomethoxysilanes and mercaptofunctional organoethoxysilanes come into consideration with particular preference. Mercaptosilanes having three alkoxy groups, in particular three methoxy groups, have been found to be particularly advantageous.

[0096] Particularly preferred mercaptosilanes are 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane and also 3-mercaptopropylmethyldimethoxysilane, especially 3-mercaptopropyltrimethoxysilane and 3-mercaptopropyltriethoxysilane, more preferably 3-mercaptopropyltrimethoxysilane.

[0097] However, it is also possible to use mercaptosilanes having a plurality of mercapto groups and / or a plurality of silane groups as organosilane OS.

[0098] In one or more embodiments, at least one mercaptosilane or its hydrolysis product is present in the composition of the invention after step f) in an amount of 0.1% to 2% by weight, preferably 0.15% to 1.5% by weight, particularly preferably 0.5% to 1% by weight, based on the total composition after step d).

[0099] If the organosilane OS is a mixture of different organosilanes, and if these organosilanes are not sensitive to cross-reactions with one another, they can be premixed in step b) and added together.

[0100] In a particularly preferred embodiment of the method according to the invention, at least one mercaptosilane and at least one aminosilane are added in step b). This combination has particularly advantageous adhesion-promoting properties while being particularly storage-stable.

[0101] By contact with water, the organosilane OS is hydrolyzed slowly or rapidly during step e) or f). Even under the best optimized process conditions, transient precipitation may occur and the solution may become slightly turbid; however, if the pH is properly adjusted in step c), especially in the range of 2 to 5, this initial precipitation can be completely reversed in a short time (typically <10 min) and the solution becomes permanently transparent.

[0102] Optionally and preferably, at least one organic titanate OT is added in step b) in an amount of 0.01 to 0.8 parts by weight of titanium.

[0103] Preferably, in addition to the organosilane OS, 0.1 to 5 parts by weight of at least one organotitanate OT are added in step b).

[0104] The organic titanate OT optionally but preferably added in step b) is in particular an alcohol-soluble, in particular ethanol-soluble organic titanate or is capable of forming alcohol-soluble titanate species under acidic and / or hydrolytic conditions. The use of organic titanates in the pretreatment composition generally leads to particularly thermally stable bonds, which show excellent bonding properties even below room temperature, and generally improves the bonding-promoting properties of the resulting pretreatment composition, in particular under hot weather conditions.

[0105] A suitable and preferred amount of organic titanate OT or its hydrolysate in the composition is preferably 0.1 to 4 wt %, in particular 0.5 to 3.5 wt %, most preferably 1 to 3 wt % of organic titanate OT, based on the total composition after step d).

[0106] Suitable organic titanates OT are preferably those of the formula Ti(OR) 4, i.e., comprising substituents bonded via an oxygen-titanium bond, and also comprising chelate substituents (multidentate ligands). Particularly suitable substituents bonded to the titanium atom via an oxygen-titanium bond are those selected from the group comprising alkoxy, sulfonate, carboxylate, aminoalkoxy, dialkyl phosphate, dialkyl pyrophosphate and acetylacetonate groups.

[0107] Particularly suitable compounds to be used as organic titanates OT are those in which all substituents bonded to the titanium are selected from the group comprising alkoxy groups, sulfonate groups, carboxylate groups, aminoalkoxy groups, dialkylphosphate groups, dialkylpyrophosphate groups and acetylacetonate groups, wherein all substituents may be identical or different.

[0108] Alkoxy groups which have been found to be particularly suitable are, in particular, methoxy, ethoxy, propoxy, isopropoxy, butoxy and isobutoxy substituents.

[0109] Particularly preferred organotitanates OT have substituents selected from alkoxy, in particular isopropoxy, and aminoalkoxy, in particular 2-(2-aminoethylamino)ethoxy, or mixtures of these substituents.

[0110] The most preferred organic titanate OT is a tetraalkoxy titanate, particularly tetra-n-butyl titanate or tetraisopropyl titanate.

[0111] Suitable organotitanium compounds to be used as organotitanate OT are commercially available, for example from Kenrich Petrochemicals or DuPont.

[0112] The most preferred organic titanate OT is tetra-n-butyl titanate or tetra-isopropyl titanate.

[0113] Optionally and preferably, at least one organic zirconate OZ is added in step b) in an amount of 0.01 to 0.8 parts by weight of titanium.

[0114] Preferably, in addition to the organosilane OS, 0.1 to 5 parts by weight of at least one organozirconate OZ are added in step b).

[0115] Organic zirconates OZ are organic zirconium compounds having at least one substituent bonded to the zirconium atom via an oxygen-zirconium bond.

[0116] Suitable organozirconate OZ compounds are especially those which carry at least one functional group selected from the group comprising alkoxy groups, sulfonate groups, carboxylate groups, phosphate groups or mixtures thereof and which is bonded directly to the zirconium atom via an oxygen-zirconium bond.

[0117] Organic zirconate OZ compounds are commercially available, for example from Kenrich Petrochemicals. Preferred are tetraalkoxy zirconates, in particular tetra-n-butyl zirconate.

[0118] It is clear to the person skilled in the art that these organic titanate OT and organic zirconate OZ compounds hydrolyze under the influence of water and form OH groups bonded to the titanium or zirconium atoms. Such hydrolyzed or partially hydrolyzed organic titanium compounds and organic zirconium compounds can then further condense themselves and form condensation products with Ti—O—Ti, Zr—O—Zr bonds. When silanes and / or titanates and / or zirconates are mixed as adhesion promoters, mixed condensation products with Si—O—Ti, Si—O—Zr or Ti—O—Zr bonds are also possible. Small proportions of such condensation products are possible, especially when they are soluble, emulsifiable or dispersible.

[0119] Step c) of the process according to the invention involves adding an acid A in such an amount that a pH of 3.5 to 7 is obtained to a mixture of alcohol, in particular ethanol, and optionally water and organosilane OS and optionally organotitanate OT and optionally organozirconate OZ.

[0120] The resulting pH of the ethanol composition after step c) is preferably from 4 to 6.5, in particular from 4.5 to 6. It is recommended to measure the pH at this stage, for example by using a pH meter or pH indicator paper, and to adjust the pH within the just specified range if necessary by further addition of acid A. The necessary amount of acid also depends on the type and amount of the ingredients added in step b), as for example aminosilanes have basic functional groups which require additional acid in order to establish the desired pH.

[0121] Acid A can be organic or inorganic. Organic acid A is firstly a carboxylic acid, especially a carboxylic acid selected from the group comprising formic acid, acetic acid, propionic acid, trifluoroacetic acid, oxalic acid, malonic acid, succinic acid, maleic acid, fumaric acid and citric acid, and amino acids, especially aspartic acid and glutamic acid. The preferred carboxylic acid is acetic acid.

[0122] Organic acids A are secondarily especially those which contain sulfur atoms. Such organic acids are especially organic sulfonic acids. Organic sulfonic acids are understood to mean compounds which contain organic radicals having carbon atoms and have at least one functional group -SO3H. Aromatic sulfonic acids are preferred.

[0123] The aromatic sulfonic acid may be monocyclic or polycyclic and one or more sulfonic groups may be present. This may be, for example, naphthalene-1-sulfonic acid or naphthalene-2-sulfonic acid, naphthalene-1,5-disulfonic acid, benzenesulfonic acid or alkylbenzenesulfonic acid.

[0124] The acid A can also be an inorganic acid. Suitable inorganic acids A are, for example, those having a sulfur atom or a phosphorus atom. Acids having a phosphorus atom are especially phosphoric acid, phosphorous acid, phosphonic acid, phosphinous acid. Acids having a sulfur atom are especially sulfuric acid, especially sulfuric acid, sulfurous acid, persulfuric acid, disulfuric acid (=pyrosulfuric acid), pyrosulfurous acid, dithionic acid, dithionous acid, thiosulfuric acid or thiosulfurous acid.

[0125] Most preferably, in particular, a pK of 4.0 to 5.0 is contemplated. a A water-soluble or at least water-miscible acid A. pK a should be understood by chemists in a manner known to mean the acid dissociation constant K a The negative decadic logarithm of: pK a =-log 10 K a .

[0126] Most preferably the acid A is a carboxylic acid, especially a water-soluble carboxylic acid, especially acetic acid.

[0127] Once step c) is completed, step d) can be started, i.e., adding water, wherein the amount of water added is at least equimolar or in molar excess to the molar amount of hydrolyzable silicon-bonded groups, titanium-bonded groups and / or zirconium-bonded groups present in all added organosilane OS, organotitanate OT and organozirconate OZ, wherein the amount of water is at most 25 parts by weight.

[0128] This amount defining the lower limit of the range (i.e., the equimolar amount mentioned above) should generally be calculated at least approximately based on all Si-OR, Ti-OR and Zr-OR groups theoretically present in the composition, wherein the term -OR means a hydrolyzable group on the corresponding Si, Ti, or Zr atom.

[0129] It is straightforward for the skilled person to calculate the appropriate amount based on the molecular structure and the added amount of each added organosilane OS, organotitanate OT, or organozirconate OZ.

[0130] Water must be added in an amount capable of completely hydrolyzing all the hydrolyzable substances contained in the composition. In this way, the resulting composition is highly active as a pretreatment to promote adhesion, including for low temperature applications, and is moreover insensitive to further exposure to water in contact with the composition. As expected, hydrolysis generates Si-OH, Ti-OH, or Zr-OH groups in the composition, and in particular compounds having -Si(OH3) groups and optionally but preferably Ti(OH4) groups are present, which are generated by the hydrolysis of trialkoxysilane-functional compounds and Ti(OR)4 compounds, respectively.

[0131] In a preferred embodiment of the process according to the invention, the composition after step f) of the process contains from 0.2 to 2.0% by weight of Si(OH) 3 groups, based on the total weight of the composition.

[0132] In a preferred embodiment of the process according to the invention, the composition after step f) of the process contains from 0.05 to 1.5 wt.-% Ti(OH)4 groups, based on the total weight of the composition.

[0133] The water to be used in step d) is preferably deionized water, in particular obtained by distillation or by reverse osmosis using the common such methods known in the art.

[0134] Step d) can be accomplished in a very easy manner and within a few minutes. Preferably, some stirring or shaking may be employed to ensure homogeneous mixing and rapid disappearance of any temporary precipitation or turbidity that may be present.

[0135] In a preferred embodiment of the process according to the invention, the amount of water added in step d) is from 0.3% to 2% by weight, based on the total composition after step d).

[0136] In a further preferred embodiment of the process according to the invention, the amount of water added in step d) is from 0.3% to 15% by weight, based on the total composition after step d).

[0137] Step e) involves the optional addition of further additives selected from colorants, UV markers, condensation catalysts, or stabilizers, or even other commonly added additives, to the activator pretreatment composition.

[0138] The additives added in step e) should not impair the storage stability of the composition. Common further components are, in particular, catalysts, stabilizers, surfactants, acids, dyes and pigments.

[0139] In some cases, it may be advantageous to add a polyisocyanate or a polyurethane prepolymer having isocyanate groups to the composition in step e).

[0140] However, it has been found to be advantageous if the composition of the invention is free of isocyanates, ie no substances having reactive NCO groups are added in step e).

[0141] As mentioned before, step e) is completely optional. It may even be advantageous not to add further ingredients after step d), since the composition obtained after step f) but omitting step e) is already a fully functionalized and highly active adhesion-promoting pretreatment and can be prepared using only basic and cost-effective ingredients, while having all the advantages of the invention, including excellent storage stability.

[0142] However, in a preferred embodiment, during step e), a silane condensation catalyst, in particular a water-soluble tin catalyst, is added to the composition. Such catalysts are known to those skilled in the art of silane-based pretreatment compositions. Once the pretreatment composition is applied to the surface, the addition of a catalyst promotes the condensation reaction of the active ingredients, and this can be helpful, in particular, when using particularly fast-curing binders and / or when the ambient temperature is particularly low during application. Surprisingly, unlike classic solvent-based adhesion promoters, the addition of such a catalyst does not impair the storage or handling stability of the composition according to the invention.

[0143] In a particularly preferred embodiment of the process according to the invention, the composition after step e) comprises, based on the total composition:

[0144] - 80 to 95% by weight of said alcohol, in particular ethanol;

[0145] - 1 to 3.5% by weight of organosilane OS;

[0146] - 1 to 3.5% by weight of an organic titanate OT;

[0147] - 0.3 to 2% by weight of acid A, in particular acetic acid;

[0148] - 0.3% to 15% by weight of water; and

[0149] - optionally 0.01 to 0.2% of a silane condensation catalyst, in particular a water-soluble tin catalyst;

[0150] The organosilane OS and the organotitanate OT can be partially or completely hydrolyzed by the water in the composition.

[0151] Such compositions are particularly process-stable and storage-stable, but are particularly reactive and highly effective as adhesion-promoting pretreatments. Such compositions are particularly suitable as pretreatments in AGR applications, which are independent of the ambient climate and the binders used in the process.

[0152] Another aspect of the invention is an adhesion-promoting pretreatment composition obtained by the process according to the invention as described above, wherein all of the added organosilane OS and optionally added organotitanate OT and optionally added organozirconate OZ are completely hydrolyzed.

[0153] A further aspect of the invention is the use of an adhesion promoting pretreatment composition according to the invention as an adhesion promoter or activator. This aspect is discussed further below in particular.

[0154] In a particularly preferred embodiment of such use according to the invention, at least one of the substrates to be treated with the adhesion-promoting pretreatment composition is a glass or glass-ceramic substrate, in particular in automotive glass repair applications.

[0155] The use according to the invention is in particular with polyurethane binders or binders based on silane-functional polymers.Silane-functional polymers encompass silicones (polydimethylsiloxanes) as well as organosilane-functional polymers such as so-called MS polymers, silane-functional polyurethanes and other silane-functional organic polymers.

[0156] The composition obtained by the process of the invention is in particular a one-component adhesion-promoting pretreatment composition. In this sense, when used as a pretreatment, the composition improves the adhesion of the adhesive to the substrate.

[0157] It has now been found that the adhesion-promoting pretreatment composition of the present invention can be used extremely efficiently for preparing an adhesive primer coating on a substrate S1 at a low substrate temperature, i.e. below 5° C. It has also been found that, in particular at a substrate temperature of 0° C. to -20° C., preferably -5° C. to -15° C., an excellent adhesive primer coating can be obtained.

[0158] Therefore, in a further aspect, the present invention also relates to a method for preparing a substrate S1 coated with the adhesion promoting pretreatment composition according to the present invention, comprising the following steps:

[0159] The adhesion-promoting pretreatment composition as described above is applied to a substrate S1 , which in particular has a temperature of less than 5°C, especially from 0°C to -20°C, preferably from -5°C to -15°C.

[0160] Possible substrates S1 are in principle most natural or synthetic substrates. If necessary, they can be pretreated before the application of the adhesion-promoting pretreatment composition. Such pretreatments include, in particular, physical and / or chemical cleaning methods, such as grinding, sandblasting, brushing, etc., or treatment with detergents or solvents; or the application of additional adhesion promoters, additional adhesion promoter solutions or primers; or flame or plasma treatments, in particular air plasma pretreatments at atmospheric ambient pressure.

[0161] More particularly, the substrate S1 is a mineral substrate, a plastic or a metal substrate.

[0162] Preferred mineral substrates are especially glass or glass ceramics, especially in the form of panes.

[0163] Preferred plastics are especially polyvinyl chloride (PVC), polyurethanes, poly(meth)acrylates, especially in the form of a coating or paint.

[0164] Metal substrates are understood here to mean metals, metal alloys and coating metals and metal alloys. In particular, light metals, non-ferrous metals and ferrous metals and their alloys are suitable, such as aluminum, iron, copper, zinc, their alloys, in particular brass and steel.

[0165] The adhesion promoting pretreatment composition may be applied by means of a cloth, felt, roller, spray, sponge, brush, dip, etc., and may be applied manually or by means of a robot.

[0166] The adhesive can be applied to the substrate coated with the bonding promoting pretreatment composition in this way. Therefore, in a further aspect, the present invention relates to a method for adhesive bonding of two substrates S1 and S2. For this purpose, there are different possibilities: in a first variant, it comprises the following steps:

[0167] a) applying an adhesion-promoting pretreatment composition as previously described to a first substrate S1 , the first substrate S1 in particular having a temperature of less than 5° C., in particular from 0° C. to -20° C., preferably from -5° C. to -15° C.;

[0168] b) applying a binder to the dried adhesion-promoting pretreatment composition applied in step a);

[0169] c) contacting the adhesive with the second substrate S2.

[0170] In a second variant, it comprises the following steps:

[0171] a′) applying an adhesion-promoting pretreatment composition as described above to a first substrate S1 , which first substrate S1 has in particular a temperature of less than 5° C., in particular from 0° C. to −20° C., preferably from −5° C. to −15° C.;

[0172] b') Applying an adhesive or sealant to the surface of the second substrate S2

[0173] c′) contacting the binder with the air-dried composition present on the substrate S1 .

[0174] In a third variant, it comprises the following steps:

[0175] a″) applying an adhesion-promoting pretreatment composition as described above to the first substrate S1 and / or the second substrate S2, which in particular has a temperature of less than 5° C., in particular from 0° C. to -20° C., preferably from -5° C. to -15° C.;

[0176] b″) applying a bonding agent to the first substrate S1 and the second substrate S2, to at least one of which a bonding-promoting pretreatment composition has been applied in step a″);

[0177] c") contacting the applied adhesives to join the substrate components to form an adhesive bond.

[0178] In a fourth variant, it comprises the following steps:

[0179] a′″) applying an adhesion-promoting pretreatment composition as described above to a first substrate S1 , which first substrate S1 has in particular a temperature of less than 5° C., in particular from 0° C. to -20° C., preferably from -5° C. to -15° C.;

[0180] b'") Allow the composition to dry

[0181] c'") Applying an adhesive between the surfaces of substrates S1 and S2.

[0182] In all four of these, the second substrate S2 is composed of the same or different material as the substrate S1.

[0183] Substrates S1 and / or S2 may be of various kinds. Possibilities for the second substrate S2 may be as described above for substrate S1. More particularly, at least one of substrates S1 or S2 is glass or glass ceramic. More particularly, one substrate is glass or glass ceramic and the other substrate is a paint or painted metal or a painted metal alloy. Thus, substrate S1 or S2 is glass or glass ceramic and substrate S2 or S1 is a paint or painted metal or a painted metal alloy.

[0184] Step c), c′), c″ or c′″) is typically followed by a step d) of curing the binder. The person skilled in the art will appreciate that, depending on the system used and the reactivity of the binder, the crosslinking reaction and thus curing can already begin during application. However, the main part of the crosslinking and therefore curing in the narrower sense of the term takes place after application, otherwise problems may also arise, namely the build-up of bonds on the substrate surface.

[0185] Useful binders are various binder systems. More particularly, they are moisture-curing binders based on prepolymers terminated with isocyanate groups and / or alkoxysilanes.

[0186] Suitable binders based on alkoxysilane-terminated prepolymers are one-component moisture-curing binders, so-called MS polymers or alkoxysilane-terminated polyurethane prepolymers, in particular such as those prepared from polyols and, if desired, polyisocyanates prepared from isocyanate-reactive organosilanes or subsequent reaction of isocyanate-functional organosilanes.

[0187] Suitable binders based on isocyanate-terminated prepolymers are understood to mean primarily two-component polyurethane binders, the first component of which comprises an amine or a polyol and the second component of which comprises an NCO-containing prepolymer or a polyisocyanate. Examples of such two-component room-temperature-curing polyurethane binders are the amines from Sika Schweiz AG, for example. Those of the product line.

[0188] Suitable adhesives based on isocyanate-terminated prepolymers are also understood to mean reactive polyurethane hot melt adhesives, which contain a thermoplastic polymer and an isocyanate-terminated prepolymer or a thermoplastic isocyanate-terminated prepolymer. Such reactive polyurethane hot melts are melted and first solidify during cooling and secondly crosslink by reaction with air humidity.

[0189] Suitable adhesives based on isocyanate-terminated prepolymers are also understood to mean one-component moisture-curing polyurethane adhesives. Such adhesives or sealants crosslink under the influence of moisture, especially air humidity. Examples of such one-component moisture-curing polyurethane adhesives are, for example, the commercially available PUMA® from Sika Schweiz AG. and Those of the product line.

[0190] The above-mentioned isocyanate-terminated prepolymers are prepared from polyols, especially polyoxyalkylene polyols, and polyisocyanates, especially diisocyanates.

[0191] Binders based on isocyanate-terminated prepolymers come into consideration preferably. Most preferred are one-component moisture-curing polyurethane binders based on isocyanate-terminated prepolymers.

[0192] It has been found that, in particular in the case of moisture-curing polyurethane adhesives or sealants, the use of the described compositions can achieve a considerable improvement in bonding, also in particular at low temperatures, i.e. in particular at temperatures of less than 5° C., in particular at temperatures of 0° C. to −20° C. Obviously, aqueous compositions may not be suitable for application temperatures of less than 0° C. due to ice formation.

[0193] These bonding methods find use in particular in the production of articles for industrial manufacture, in particular means of transport. Such articles are in particular automobiles, buses, trucks, rail vehicles, ships or aircraft.

[0194] The most preferred application is in the glazing of transport vehicles, especially road and rail vehicles.

[0195] Due to the excellent improvement in the bonding of the adhesive and sealant at low temperatures, the method is particularly suitable for glazing repair, also known as automotive glass repair (AGR) operations. In particular, vehicles can be glazed on site on the street, especially also in winter, without having to first place the vehicle in a temperature-controlled garage. This is particularly important for repairing vehicle panes in remote areas, especially where roads typically have loose stones or gravel. Such areas are typically found in, for example, Scandinavia, Russia, China, Argentina, Chile, Canada or the United States. The adhesive basecoat composition is particularly suitable for a method for repairing glazing of transport means, especially automobiles, at an ambient temperature of less than 5°C, especially from 0°C to -20°C, preferably from -5°C to -15°C, comprising the following steps

[0196] i) Removal of defective glass, especially defective window panes;

[0197] ii) applying the bonding-promoting pretreatment composition as described above to the glass sheets, in particular panes, to be inserted by adhesive bonding, and / or to the flanges of the transport means to be adhesively bonded;

[0198] iii) applying a moisture-curing one-component adhesive, in particular a moisture-curing one-component polyurethane adhesive, having a temperature of 10° C. to 80° C., in particular about 23° C., to the glass sheet to be adhesively bonded and / or to the flange of the transport means to be adhesively bonded;

[0199] iv) Joining the glass and the flange via the adhesive present therebetween.

[0200] It has been found that by means of this method, in cold conditions such as often occur during winter, a vehicle can be glazed on site, on the street, without first having to place the vehicle in a temperature controlled garage. This is particularly important for servicing vehicle panes in remote areas, especially where the streets often have loose stones or gravel. Such areas are often found in, for example, Scandinavia, Russia, China, Argentina, Chile, Canada or the United States.

[0201] Since the adhesion-promoting pretreatment composition according to the invention also promotes adhesion at higher temperatures, i.e. at temperatures >5°C, typically around room temperature (23°C) up to about 45°C or higher, one and the same adhesion-promoting pretreatment composition can be used, thus avoiding the necessity of different operating modes for summer products and winter products or according to the season.

[0202] Example

[0203] The present invention is further illustrated by the following examples, which are not intended to limit the invention in any way.

[0204] Raw materials used

[0205] The following raw materials listed in Table 1 were used as commercially available without further purification or modification, and were used in the method according to the present invention to prepare the adhesion promoting pretreatment compositions of the examples in order to illustrate the effects of the present invention.

[0206]

[0207]

[0208] Table 1: Raw materials used.

[0209] Example Preparation of Compositions C1 to C22

[0210] Example compositions C1-C22 were prepared in sequential order using the steps of the following procedure and involved the raw materials listed in Table 1. The corresponding composition details of each composition C1 to C22 are shown in Tables 2 to 5. In each table, the numbers indicate the amount of each corresponding raw material / ingredient added (in parts by weight). Compositions not according to the invention are indicated in Tables 2 to 5 with an asterisk (*).

[0211] The following method was performed in a standard climate chamber (23° C., 50% relative humidity (rh)) without heating the reaction vessel.

[0212] Step a)

[0213] An open glass beaker equipped with a magnetic stirrer was filled with the corresponding indicated amounts of ethanol and, where applicable, additional solvent.

[0214] Step b)

[0215] In each respective experiment, all organosilane OS, organotitanate OT, and / or organozirconate OZ raw materials were added stepwise under stirring in order and in the amounts as listed in the respective Tables 2 to 5.

[0216] Step c)

[0217] In each respective experiment, acid A was added in the amount as listed in respective Tables 2 to 5.

[0218] Step d)

[0219] In each respective experiment, water was added in the amounts listed in respective Tables 2 to 5.

[0220] Step f)

[0221] The resulting mixture was stirred at 23°C for at least 30 min until a clear, homogeneous solution was obtained.

[0222] Each composition was then packaged into a sealable glass container and used as an adhesion promoting pretreatment for use in adhesion testing and / or artificial aging testing to evaluate storage stability.

[0223]

[0224]

[0225] Table 2: Ingredients added to compositions C1-C6 (parts by weight). * Not according to the invention.

[0226] C7 C8* C9 C10 C11* C12 Ethanol 90 90 91.9 89.9 89.9 89.9 Sil A-1170 3 5 2 3 3 4 Dynasylan A - - - - 3 - Tyzor TnBT 3 1 2 3 - 2 Acetic acid 2 2 2 2 2 2 water 2 2 2 2 2 2 catalyst - - 0.1 0.1 0.1 0.1

[0227] Table 3: Ingredients added to compositions C7-C12 (in parts by weight). * Not according to the invention.

[0228]

[0229]

[0230] Table 4: Ingredients added to compositions C13-C17 (in parts by weight). * Not according to the invention.

[0231] C18 C19 C20* C21 C22 Ethanol 84.9 89.9 65.3 89.9 91.4 Acetaldehyde 5 - - - - Heptane - - 25 - - Sil A-1170 3 3 3 3 3 Tyzor TnBT 3 3 3 - - KR 9S - - - - 2 Tytan TNBZ - - - 3 - Acetic acid 2 2 1.6 2 2 MeSA - - 0.4 - - water 2 2 1.6 2 1.5 catalyst 0.1 0.1 0.1 0.1 0.1

[0232] Table 5: Ingredients added to compositions C18-C22 (in parts by weight). * Not according to the invention.

[0233] Test plan

[0234] Example compositions C1-C22 were tested as follows.

[0235] In order to evaluate storage stability, Example compositions C1 to C22 were subjected to simulated aging under heat. For this reason, sealed glass bottles of each respective composition were placed in an oven (50° C.) and placed under this condition for up to 2 years. Every week, the samples were checked for significant changes (precipitation, gelation, etc.). For samples C11 to C22, there is no available long-term data because they are prepared more recently. Samples that show no change in gelation, precipitation, or other degradation after at least 21 days at 50° C. are considered to be storage stable.

[0236] Composition Storage stability test results C1 No change in composition after 2 years at 50°C C2 No change in composition after 2 years at 50°C C3 No change in composition after 2 years at 50°C C4 No change in composition after 2 years at 50°C C5 No change in composition after 2 years at 50°C C6 No change in composition after 2 years at 50°C C7 No change in composition after 2 years at 50°C C8* Gel after 7 days at 50°C C9 No change in composition after 2 years at 50°C C10 No change in composition after 2 years at 50°C C11* Gel after 14 days at 50°C C12 No change in composition after >21 days at 50°C C13 No change in composition after >21 days at 50°C C14 No change in composition after >21 days at 50°C C15* Gel after 7 days at 50°C C16* Gel after 7 days at 50°C C17* Gel after 21 days at 50°C C18 No change in composition after >21 days at 50°C C19 No change in composition after >21 days at 50°C C20* Gel after 7 days at 50°C C21 No change in composition after >21 days at 50°C C22 No change in composition after >21 days at 50°C

[0237] Table 6: Results of storage stability tests on compositions C1-C22. *Not according to the invention

[0238] Adhesion Testing Solution

[0239] This test protocol studies the adhesion-promoting ability of example compositions (both examples according to the invention and reference examples not according to the invention) prepared with the method specified above and additionally two commercial solvent-based activators as reference of the prior art.

[0240] The adhesive used in this test protocol is ELITE, which is a commercially available one-component moisture-curing polyurethane adhesive, contains a polyurethane prepolymer having isocyanate groups and is commercially available from Sika Schweiz AG.

[0241] Additional reference adhesion promoting pre-treatments used (currently used prior art activators) are:

[0242] "MP-A", a multi-purpose solvent-based activator particularly suitable for glass and ceramic substrates ("MP-A"), and

[0243] “AGR-A”, a solvent-based activator optimized for AGR applications, including low-temperature glass replacement (“AGR-A”).

[0244] Two reference activators MP-A and AGR-A were prepared by adding the corresponding silanes to the corresponding solvents. The detailed ingredients and their amounts (in parts by weight) are shown in the following Table 7:

[0245] MP-A* AGR-A* Heptane 93.9 80.8 Ethanol - 15.0 Sil A-1170 6.0 4.0 Sil A-189 0.1 - Sil A-187 - 0.2

[0246] Table 7: Ingredients added to the reference activator compositions MP-A and AGR-A (in parts by weight). * Not according to the invention.

[0247] The substrates used were: “Glass (air)”: float glass with the air side used for bonding tests, Rocholl, Germany; “Glass (tin)”: float glass with the tin side used for bonding tests, Rocholl, Germany; “Frit 3402”: ESG ceramic, Ferro AD 3402, Rocholl, Germany; “Ferro 14279”: VSG ceramic, Ferro 14279, Rocholl, Germany; “Ferro 14303”: VSG ceramic, Ferro 14303IR7134, Rocholl, Germany.

[0248] Immediately before applying the adhesion promoter composition, the All substrate surfaces were cleaned by wiping off a cellulose cloth that was soaked with isopropyl alcohol and allowed to dry for at least 2 minutes prior to application of the respective adhesion promoting pretreatment composition to be tested.

[0249] The composition to be tested was placed on a cellulose cloth ( The adhesive was applied to the specific substrates with a 5-min drying time before the adhesive was applied to the thus pretreated surface ("wipe" application). In most cases, the substrates were conditioned at 23° C. before application of the composition, but in some cases at 5° C. to study the low-temperature application behavior. The exact application conditions used for each experiment are shown in Tables 7 to 11.

[0250] A triangular bead of adhesive was applied at 23° C.±2° C. and 50% relative air humidity by means of a press box and a nozzle. Prior to application, the adhesive itself was allowed to equilibrate in a closed box at 23° C. for 24 h.

[0251] After the curing time specified in each experiment (Tables 7 to 11), the cured bonds with the adhesive were tested under controlled climate conditions (23° C., 50% relative air humidity) for 45 min to 7 days (e.g., “45 min RT”), or cured soaked in water for 7 days to evaluate the water stability of the adhesive bond (“7d water”).

[0252] The bonding of the adhesive is tested by means of the 'bead bonding test'. This involves cutting into a bead at its end just above the bonding surface. The cut end of the bead is fixed with round nose pliers and pulled away from the substrate. This is done by carefully rolling the bead onto the tip of the pliers and cutting at right angles to the direction in which the bead is pulled downwards towards the exposed substrate. The bead pulling speed should be selected so that a cut is made approximately every 3 seconds. The test distance must correspond to at least 8 cm. What is evaluated is the adhesive that remains on the substrate after the bead has been pulled apart (cohesive fracture). The bonding properties are evaluated by visually determining the bonding fraction of the bonding area.

[0253] In this test protocol, the amount of cohesive failure is evaluated (based on the overall fracture pattern, in %) and expressed numerically (0% CF to 100% CF, where "CF" stands for "cohesive failure").

[0254] The higher the proportion of cohesive failures, the better the assessment of the adhesive bond.Ideally, the bond shows 100% CF.

[0255] The results of these bonding tests for the bonding promoting pretreatment compositions tested on separate test substrates are shown in Tables 8 to 12.

[0256]

[0257] Table 8: Adhesion test results for the test regimens. * Not according to the invention.

[0258]

[0259]

[0260] Table 9: Adhesion test results for the test regimens. * Not according to the invention.

[0261]

[0262] Table 10: Adhesion test results for the test regimen. * Not according to the invention.

[0263] Tables 8 to 10 show that the compositions according to the invention show an improved adhesion promoting effect on the tested substrates compared to similar compositions not according to the invention. Compared to the commercial benchmark activator (MP-A), the compositions according to the invention perform at least as well if not better under ambient curing conditions. With regard to the bonding results under water, the compositions according to the invention clearly have improved properties compared to the commercial activator.

[0264]

[0265] Table 11: Adhesion test results for the test regimens. * Not according to the invention.

[0266] The results in Table 11 demonstrate that the example composition C10 according to the invention leads to excellent bonding both at short (1 h) or long (7 d) curing times compared to the commercial (AGR-A) and example (C11) reference compositions. The composition of the invention is once again superior, especially in terms of water resistance of the adhesive bond.

[0267]

[0268] Table 12: Adhesion test results for the test regimens. * Not according to the invention.

[0269] Table 12 compares the composition of the invention (C12) with two commercial activators with respect to their low temperature application. As can be seen, the composition according to the invention even slightly exceeds the performance of AGR-A (activator optimized for temperature-independent AGR applications).

[0270] Bond Testing Using Aged Bond Promoting Pretreatment Compositions

[0271] Additional adhesion tests were performed using Example composition C10 (one freshly prepared sample and one aged by opening the bottle at 35° C. and 80% rh for 40 minutes). As a reference, AGR-A (see above) was used, also with both fresh samples and samples artificially aged in the same way.

[0272] These bonding tests were done on the following samples: "Glass (Air)": float glass where the air side was used for the bonding tests, Rocholl, Germany; "Glass (Tin)": float glass where the tin side was used for the bonding tests, Rocholl, Germany.

[0273] The adhesive used is PRO, a one-component polyurethane adhesive for AGR applications, is available from Sika Schweiz.

[0274] The bond test was performed in the same manner as the first bond test protocol described above.In addition, the bond test was performed after curing the adhesive bond in an oven at 80°C ("1d 80°C") for 1 day.

[0275] The results are shown in Table 13.

[0276]

[0277]

[0278] Table 13: Adhesion test results for the test regimens. * Not according to the invention.

[0279] The results shown in Table 13 confirm that the composition of the invention does not lose its properties after aging and shows the same bonding promotion effect as in the fresh state regardless of the application temperature and curing conditions of the adhesive bond. On the other hand, the reference composition shows some loss of properties after artificial aging.

Claims

1. A method for preparing a bonding promoting pretreatment composition, comprising the following steps: a) providing a reaction container containing 100 parts by weight of an alcohol having 1 to 4 carbon atoms; b) adding at least one organosilane OS in an amount to add 0.15 to 0.8 parts by weight of silicon, and optionally at least one organotitanate OT in an amount to add 0.01 to 0.8 parts by weight of titanium, and optionally at least one organozirconate OZ in an amount to add 0.01 to 0.8 parts by weight of zirconium; c) adding acid A in an amount such that the resulting pH is between 3.5 and 7; d) adding water, wherein the amount of water added is at least equimolar or in molar excess to the molar amount of hydrolyzable silicon-bonded groups, hydrolyzable titanium-bonded groups and / or hydrolyzable zirconium-bonded groups present in all added organosilanes OS, organotitanates OT and organozirconates OZ, wherein the amount of water is at most 25 parts by weight; e) optionally, adding further additives selected from colorants, UV markers, condensation catalysts, or stabilizers; f) waiting, optionally with stirring, shaking and / or heating, until all hydrolyzable groups present in all added organosilanes OS, organotitanates OT and organozirconates OZ have been hydrolyzed.

2. The method according to claim 1, characterized in that The acid A in step c) is a carboxylic acid or an alkylsulfonic acid, preferably acetic acid or methanesulfonic acid, in particular acetic acid.

3. The method according to claim 1 or claim 2, characterized in that: The organosilane OS comprises at least one organosilane or a condensate thereof which has at least one Si-bonded hydrolyzable group and has at least one primary and / or secondary amino group.

4. The method according to any one of claims 1 to 3, characterized in that The organosilanes OS comprise organosilanes or oligomers of these organosilanes having at least one Si-bonded hydrolyzable group and having at least one further functional group bonded to the silicon atom via at least one carbon atom and optionally an ether oxygen or nitrogen atom, the functional group being selected from alkyl, alkylene, phenyl, epoxy, mercapto, hydroxyl, (meth)acrylate, isocyanate, anhydride, silane and isocyanurate groups.

5. The method according to any one of claims 1 to 4, characterized in that The organic titanate OT is a tetraalkoxy titanate, in particular tetra-n-butyl titanate or tetraisopropyl titanate.

6. The method according to any one of claims 1 to 5, characterized in that The organic zirconate OZ is a tetraalkoxy zirconate, in particular tetra-n-butyl zirconate.

7. The method according to any one of claims 1 to 6, characterized in that The alcohol having 1 to 4 carbon atoms is ethanol.

8. The method according to any one of claims 1 to 7, characterized in that In step c), acid A is added in such an amount that the resulting pH is from 4 to 6.5, in particular from 4.5 to 6.

9. The method according to any one of claims 1 to 8, characterized in that The amount of water added in step d) is 0.3% to 15% by weight, based on the total composition after step d).

10. The method according to any one of claims 1 to 9, characterized in that In step e), a silane condensation catalyst, in particular a water-soluble tin catalyst, is added.

11. The method according to any one of claims 1 to 10, characterized in that Based on the total composition, after step e), the composition comprises: - 80 to 95% by weight of said alcohol, in particular ethanol; - 1 to 3.5% by weight of organosilane OS; - 1 to 3.5% by weight of an organic titanate OT; - 0.3 to 2% by weight of acid A, in particular acetic acid; - 0.3% to 15% by weight of water; and - optionally 0.01 to 0.2% of a silane condensation catalyst, in particular a water-soluble tin catalyst; The organosilane OS and the organotitanate OT may be partially or completely hydrolyzed by the water in the composition. 12 . Adhesion-promoting pretreatment composition obtainable by the process as claimed in claim 1 , wherein all of the added organosilane OS and optionally added organotitanate OT and optionally added organozirconate OZ are completely hydrolyzed.

13. Use of the adhesion promoting pretreatment composition according to claim 12 as an adhesion promoter or activator.

14. The use according to claim 13, wherein At least one of the substrates to be treated with the adhesion promoting pretreatment composition is a glass substrate or a glass ceramic substrate, particularly in automotive glass repair applications.

15. The method according to claim 13, wherein the binder is a polyurethane binder or a binder based on a silane-functional polymer.

Citation Information

Patent Citations

  • Surface coating composition

    WO2006049368A1

  • Low-temperature adhesive undercoat composition

    WO2008061981A1

  • Water based primer composition for bonding glass into a structure

    WO2013116004A1